Lead acid battery

By incorporating a higher concentration of a specific polymer compound in the center of the negative electrode plate, the lead-acid battery reduces overcharging effects and maintains high-rate discharge performance at low temperatures, addressing battery degradation and electrolyte loss issues.

JP7661690B2Active Publication Date: 2025-04-15GS YUASA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020197589
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-27
Publication Date
2025-04-15
Estimated Expiration
2040-11-27

AI Technical Summary

Technical Problem

Lead-acid batteries experience deterioration and reduced electrolyte levels due to overcharging, leading to increased battery degradation.

Method used

The battery design includes a negative electrode plate with a higher concentration of a specific polymer compound in the center, which suppresses hydrogen gas generation and reduces overcharging effects, while maintaining high-rate discharge performance at low temperatures.

Benefits of technology

This configuration results in a lead-acid battery with reduced overcharged electricity and improved low-temperature high-rate discharge performance, effectively addressing the issues of battery degradation and electrolyte loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661690000003
    Figure 0007661690000003
  • Figure 0007661690000004
    Figure 0007661690000004
  • Figure 0007661690000005
    Figure 0007661690000005
Patent Text Reader

Abstract

To provide a lead acid battery having a small amount of overcharge electricity.SOLUTION: A lead acid battery 1 includes a positive electrode plate 3 and a negative electrode plate 2. The negative electrode plate 2 includes a negative electrode current collector 2a and a negative electrode material supported by the negative electrode current collector. The negative electrode material includes a first negative electrode material, and a second negative electrode material arranged outside the first negative electrode material. The content (ppm) of the polymer compound in the first negative electrode material is higher than the content (ppm) of the polymer compound in the second negative electrode material. The polymer compound has a peak in the range of 3.2 ppm or more and 3.8 ppm or less in the chemical shift of the 1H-NMR spectrum measured using deuterated chloroform as a solvent.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lead-acid battery. [Background technology]

[0002] Lead-acid batteries are used in a variety of applications, including automotive and industrial use. Lead-acid batteries typically include a negative plate, a positive plate, a separator (or mat), and an electrolyte. Typically, each plate includes a current collector and an electrode material supported by the current collector.

[0003] The electrode material of the electrode plate usually has a uniform composition overall. Meanwhile, Patent Document 1 (JP Patent Publication 59-042771) discloses a method for producing a positive plate for a lead-acid battery, which comprises forming a layer in which fine particles of a thermoplastic resin are dispersed on the surface of a grid, and then filling the grid with a paste for a positive electrode containing fine particles of a thermoplastic resin.

[0004] Patent Document 2 (JP 2000-149981 A) discloses a lead-acid battery characterized in that the electrolyte and / or the electrode active material molded body contain a polymer compound containing any one selected from the group consisting of polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, polyacrylic acid, or esters thereof, each having a degree of polymerization of 30 to 3000, or the polymer compound and colloidal barium sulfate particles.

[0005] Patent Document 3 (JP Patent Publication 9-147874 A) discloses a negative electrode plate for a lead-acid battery, in which a paste-type active material containing a shrinkage inhibitor is filled into a current collector, and the shrinkage inhibitor is polyoxyperfluoroethylenephenylamine represented by a specific chemical formula, and the polyoxyperfluoroethylenephenylamine is contained in an amount of 0.005 to 3% by weight relative to the paste-type active material. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 59-042771 [Patent Document 2] JP 2000-149981 A [Patent Document 3] Japanese Patent Application Publication No. 9-147874 Summary of the Invention [Problem to be solved by the invention]

[0007] In lead-acid batteries, overcharging can cause deterioration of the positive electrode current collector and a decrease in the electrolyte, etc. Therefore, if the amount of overcharging electricity is large, the deterioration of the battery is likely to be accelerated. [Means for solving the problem]

[0008] One aspect of the present invention relates to a lead-acid battery, the lead-acid battery including a positive electrode plate and a negative electrode plate, the negative electrode plate including a negative electrode current collector and a negative electrode material supported by the negative electrode current collector, the negative electrode material including a first negative electrode material in contact with the negative electrode current collector and a second negative electrode material disposed on the outer side of the first negative electrode material, the content (ppm) of a polymer compound by mass in the first negative electrode material being greater than the content (ppm) of the polymer compound by mass in the second negative electrode material, the polymer compound being measured using deuterated chloroform as a solvent. 1 In the H-NMR spectrum, it has a peak in the range of 3.2 ppm to 3.8 ppm.

[0009] Another aspect of the present invention relates to another lead-acid battery, the other lead-acid battery including a positive electrode plate and a negative electrode plate, the negative electrode plate including a negative electrode collector and a negative electrode material supported by the negative electrode collector, the negative electrode material including a first negative electrode material in contact with the negative electrode collector and a second negative electrode material disposed on the outer side of the first negative electrode material, the content (ppm) of a polymer compound in the first negative electrode material being greater than the content (ppm) of the polymer compound in the second negative electrode material, the polymer compound being oxy-C2-4 It contains a repeating structure of alkylene units. Effect of the Invention

[0010] According to the present invention, a lead-acid battery with a small amount of overcharge electricity can be obtained. [Brief description of the drawings]

[0011] [Figure 1] 1 is a partially cutaway exploded perspective view showing the appearance and internal structure of a lead-acid battery according to one aspect of the present invention. FIG. [Figure 2A] FIG. 2 is a cross-sectional view of an example of a negative electrode plate of a lead-acid battery according to one aspect of the present invention. [Figure 2B] 2B is a cross-sectional view of the negative electrode plate shown in FIG. 2A taken along line IIB-IIB. [Diagram 3] FIG. 4 is a cross-sectional view of another example of a negative electrode plate of a lead-acid battery according to one aspect of the present invention. [Figure 4] 1 is a graph showing some of the results of the examples. [Diagram 5] 11 is a graph showing another part of the results of the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In the following, the embodiment of the present invention will be described with examples, but the present invention is not limited to the examples described below. In the following description, specific numerical values ​​and materials may be exemplified, but other numerical values ​​and materials may be applied as long as the effects of the present invention can be obtained. In this specification, when "numerical value A to numerical value B" is mentioned, the range includes numerical value A and numerical value B.

[0013] (lead acid battery) The lead-acid battery according to the present embodiment includes a positive electrode plate and a negative electrode plate. The negative electrode plate includes a negative electrode collector and a negative electrode material supported by the negative electrode collector. The negative electrode material includes a first negative electrode material and a second negative electrode material disposed outside the first negative electrode material. The content (ppm) of the polymer compound in the first negative electrode material is greater than the content (ppm) of the polymer compound in the second negative electrode material. Hereinafter, the polymer compound may be referred to as a "polymer compound (P)". Hereinafter, the content of the polymer compound (P) means the content (ppm, content) in the mass standard unless otherwise specified.

[0014] The first example of the polymer compound (P) is measured using deuterated chloroform as a solvent. 1 It is a polymer compound having a peak in the range of 3.2 ppm to 3.8 ppm in the chemical shift of the H-NMR spectrum. 1 Unless otherwise specified, the H-NMR spectrum was measured using deuterated chloroform as a solvent. 2-4 It is a polymer compound containing a repeating structure of an alkylene unit. The polymer compound included in the first example of the polymer compound (P) and the polymer compound included in the second example of the polymer compound (P) overlap at least partially. The polymer compound (P) may be a commercially available product. Alternatively, the polymer compound (P) may be synthesized by a known method.

[0015] The second negative electrode material is disposed on the outside (outside in the thickness direction of the negative electrode plate) of the first negative electrode material. The second negative electrode material may be disposed only on the outside of one of the first negative electrode materials. Alternatively, the second negative electrode material may be disposed on the outside of both of the first negative electrode materials. In this case, the second negative electrode material is disposed so as to sandwich the first negative electrode material. In one aspect, the content (ppm) of the polymer compound (P) based on mass in the negative electrode material is higher in the center in the thickness direction of the negative electrode plate than in the surface side of the negative electrode plate. Hereinafter, the center in the thickness direction of the negative electrode plate may be simply referred to as the "center of the negative electrode plate". The first negative electrode material may be in contact with the negative electrode current collector.

[0016] In lead-acid batteries, when charging, the water in the electrolyte is electrolyzed at the negative plate, generating hydrogen gas. If the amount of overcharging electricity is large, the amount of electrolyte is reduced by the electrolysis of water. In addition, if the amount of overcharging electricity is large, the deterioration of the positive electrode current collector is accelerated. Therefore, it is particularly important to reduce the amount of overcharging electricity in lead-acid batteries.

[0017] As a result of the investigation, the inventors of the present application found that by increasing the content of the polymer compound (P) in the center of the negative electrode plate, the amount of hydrogen gas generated can be particularly suppressed, and as a result, the amount of overcharge electricity can be reduced. This invention is based on this new finding. Furthermore, the inventors of the present application newly found that by increasing the content of the polymer compound (P) in the center of the negative electrode plate, the performance of high-rate discharge at low temperatures can be improved. These effects will be explained in the examples.

[0018] During overcharging, which generates more hydrogen gas, the amount of hydrogen gas generated is greater in the center of the negative plate in the thickness direction than in the surface area of ​​the negative plate. Therefore, by disposing a polymer compound (P) that acts to suppress the amount of overcharge electricity in the center of the negative plate, it is possible to particularly reduce the amount of overcharge electricity.

[0019] As described later, the polymer compound (P) covers the surface of the lead in the negative electrode material. In high-rate discharge at low temperatures, the diffusion of sulfuric acid becomes a rate-limiting factor, and the reaction occurs mainly near the surface of the negative electrode plate rather than in the center of the negative electrode plate. Therefore, if the content of the polymer compound (P) in the surface of the negative electrode plate is high, the duration of low-temperature high-rate discharge decreases rapidly. By distributing the polymer compound (P) unevenly in the center of the negative electrode plate, the content of the polymer compound (P) in the surface of the negative electrode plate can be reduced while maintaining the content of the polymer compound (P) in the entire negative electrode plate. This makes it possible to suppress the deterioration of the performance of the lead-acid battery (deterioration of the duration of low-temperature high-rate discharge) when the polymer compound (P) is added to the negative electrode material.

[0020] The reason why the polymer compound (P) can reduce the amount of overcharge electricity is considered to be as follows. 2-4 Since it contains a repeating structure of alkylene units, it is easy to have a linear structure. Therefore, the polymer compound (P) added to the negative electrode material thinly and widely covers the surface of the lead in the negative electrode material. By covering the surface of the lead with the polymer compound (P), the hydrogen overvoltage increases, and as a result, the side reaction of generating hydrogen during overcharge is less likely to occur. On the other hand, if the amount of the polymer compound (P) added is large, the charge acceptance may decrease. In the present invention, the content of the polymer compound (P) in the center of the negative electrode plate, which generates a large amount of hydrogen gas during overcharge, is high. Therefore, it is possible to effectively reduce the amount of overcharge electricity while suppressing the amount of polymer compound (P) in the entire negative electrode plate. That is, according to the present invention, high charge acceptance performance and low overcharge electricity can be realized.

[0021] The polymer compound (P) is oxyC 2-4 It is preferable that the alkylene unit contains a repeating structure. 2-4When a polymer compound (P) containing a repeating structure of alkylene units is used, it is believed that the polymer compound (P) is more easily adsorbed to lead and is more likely to have a linear structure, which makes it easier to thinly cover the lead surface. Therefore, the amount of overcharge electricity can be more effectively reduced and the effect of suppressing the decrease in charge acceptance can be further improved.

[0022] The polymer compound (P) is oxyC 2-4 The hydroxy compound may include at least one selected from the group consisting of a hydroxy compound having a repeating structure of an alkylene unit, an etherified product of the hydroxy compound, and an esterified product of the hydroxy compound. 2-4 Examples of hydroxy compounds containing repeating alkylene units will be described later.

[0023] The polymer compound (P) may be an ester of polyalkylene glycol having an alkylene group with a carbon number in the range of 2 to 4. This configuration provides a lead-acid battery with a particularly low charge quantity and particularly high low-temperature high-rate discharge performance. The polymer compound (P) may be, for example, at least one selected from the group consisting of esters of polyethylene glycol and esters of polypropylene glycol.

[0024] The negative electrode current collector may include a plurality of linear portions (or, from another point of view, thin rod-shaped portions). In this case, the first negative electrode material may be disposed in the gaps between the plurality of linear portions. The first negative electrode material may be disposed not only in the gaps but also outside the linear portions and outside the gaps. In a typical example, the negative electrode material is composed of a first negative electrode material and a second negative electrode material.

[0025] An example of the negative electrode material is composed of a first electrode material and a second electrode material, and the second electrode material is arranged so as to sandwich the first negative electrode material and the multiple linear portions. In this case, the second negative electrode material is arranged in layers on the two main surfaces of the negative electrode plate. In this case, the first negative electrode material may also be arranged in layers.

[0026] The negative electrode current collector may have a lattice portion composed of a plurality of linear portions. In this case, the first negative electrode material is disposed in the gaps between the lattices. The first negative electrode material may be disposed not only in the gaps, but also outside the lattice portion and outside the gaps. Examples of negative electrode current collectors having a lattice portion include current collectors including an expanded lattice formed by an expanding process.

[0027] The first negative electrode material may constitute a first layer portion. The second negative electrode material may constitute a second layer portion disposed outside the first layer portion. Alternatively, the boundary between the first negative electrode material and the second negative electrode material may not be clear. For example, the content of the polymer compound (P) may gradually decrease from the center in the thickness direction of the negative electrode plate toward the surface side of the negative electrode plate.

[0028] In one example, when the negative electrode material arranged on the negative plate is divided into three regions in the thickness direction, the content of the polymer compound (P) in the first region at the center may be greater than the content of the polymer compound (P) in the two second regions on both sides. The negative electrode material arranged in the first region contacts the negative electrode collector. When the thickness of the negative electrode material arranged on the negative plate is T, the thickness T1 of the first region may be in the range of 0.2T to 0.8T (for example, in the range of 0.4T to 0.7T), and the thickness T2 of one second region may be in the range of 0.1T to 0.4T (for example, in the range of 0.15T to 0.3T). The two boundaries separating the three regions may coincide with the surfaces on both sides of the negative electrode collector.

[0029] There is no particular limitation on the thickness of the negative electrode plate, and it may be in the range of 0.6 mm to 2.0 mm (for example, in the range of 1.0 mm to 1.4 mm), or may be in another range.

[0030] The content Ct(2) of the polymer compound in the second negative electrode material may be in the range of 0 to 0.7 times the content Ct(1) of the polymer compound in the first negative electrode material. This range allows a particularly well-balanced realization of high charge acceptance performance and low overcharge electricity quantity. The content Ct(2) may be 0 times or more, 0.1 times or more, or 0.3 times or more of the content Ct(1). The content Ct(2) may be 0.7 times or less, 0.5 times or less, 0.4 times or less, or 0.3 times or less of the content Ct(1). These lower and upper limits can be arbitrarily combined as long as there is no contradiction. The content Ct(2) may be in the range of 0 to 0.5 times, 0 to 0.4 times, 0.1 to 0.7 times, 0.3 to 0.7 times, or 0.1 to 0.5 times the content Ct(1).

[0031] The content of the polymer compound (P) in the first negative electrode material may be in the range of 80 ppm to 500 ppm (for example, in the range of 80 ppm to 400 ppm) by mass, which allows a particularly well-balanced realization of high charge acceptance performance and low overcharge electricity quantity.

[0032] The content of the polymer compound (P) in the negative electrode material may satisfy at least one of the following conditions (1) to (3). For example, the following conditions (1) and (2), (1) and (3), or (2) and (3) may be satisfied. Alternatively, the following conditions (1) to (3) may all be satisfied. (1) The content of the polymer compound (P) in the first negative electrode material is 40 ppm or more, 60 ppm or more, 80 ppm or more, 140 ppm or more, or 280 ppm or more by mass. The content is 1000 ppm or less, 500 ppm or less, 400 ppm or less, or 300 ppm or less by mass. These lower and upper limits can be combined arbitrarily as long as there is no contradiction. For example, the content may be in the range of 40 to 1000 ppm, 60 to 500 ppm, 60 to 400 ppm, 80 to 500 ppm, 80 to 400 ppm, or 60 to 300 ppm by mass. (2) The relationship between the content Ct(2) of the polymer compound in the second negative electrode material and the content Ct(1) of the polymer compound in the first negative electrode material satisfies the above-mentioned exemplary relationship. (3) The content of the polymer compound (P) in the entire negative electrode material is 40 ppm or more, 60 ppm or more, 80 ppm or more, 140 ppm or more, or 280 ppm or more by mass. The content is 400 ppm or less, or 300 ppm or less by mass.

[0033] The lead acid battery may be either a valve regulated (sealed) lead acid battery (VRLA type lead acid battery) or a flooded (vented) lead acid battery.

[0034] In this specification, the content of the polymer compound (P) in the negative electrode material is determined for a negative electrode plate taken out from a fully charged lead-acid battery.

[0035] (Terminology explanation) (electrode material) The negative electrode material and the positive electrode material are usually held by a current collector. The electrode material is the electrode plate excluding the current collector. A member such as a mat or pasting paper may be attached to the electrode plate. Such a member (also called an attachment member) is used integrally with the electrode plate and is therefore included in the electrode plate. When the electrode plate includes an attachment member (such as a mat or pasting paper), the electrode material is the electrode material excluding the current collector and the attachment member.

[0036] (Polymer Compound (P)) The polymer compound (P) satisfies at least one of the following conditions (i) and (ii). Condition (i) Polymer compounds (P) are measured using deuterated chloroform as a solvent. 1 In the H-NMR spectrum, it has a peak in the range of 3.2 ppm to 3.8 ppm. Condition (ii) The polymer compound (P) is oxyC 2-4It contains a repeating structure of alkylene units.

[0037] Under condition (i), the peak in the range of 3.2 ppm to 3.8 ppm is oxy-C 2-4 It is derived from an alkylene unit. In other words, the polymer compound (P) satisfying the condition (ii) is also the polymer compound (P) satisfying the condition (i). The polymer compound (P) satisfying the condition (i) is an oxyC 2-4 The polymer compound (P) may contain a repeating structure of a monomer unit other than an alkylene unit, and may have a certain molecular weight. The number average molecular weight (Mn) of the polymer compound (P) that satisfies the above (i) or (ii) may be, for example, 300 or more.

[0038] (Oxy C 2-4 Alkylene unit) Oxy C 2-4 The alkylene unit is -OR 1 - is a unit represented by R 1 is C 2-4 R represents an alkylene group (an alkylene group having 2 to 4 carbon atoms). 1 may contain alkylene groups having different numbers of carbon atoms.

[0039] (Organic shrink-proofing agent) The organic shrinkage inhibitor refers to an organic compound among compounds that have the function of suppressing the shrinkage of lead, which is the negative electrode active material, when a lead-acid battery is repeatedly charged and discharged.

[0040] (number average molecular weight) The number average molecular weight (Mn) is determined by gel permeation chromatography (GPC). The standard substance used in determining Mn is polyethylene glycol.

[0041] (Weight average molecular weight) The weight average molecular weight (Mw) is determined by GPC. The standard substance used in determining Mw is sodium polystyrene sulfonate.

[0042] (Sulfur content in organic shrinkage inhibitors) The content of sulfur element in an organic shrink-preventer being X μmol / g means that the content of sulfur element contained in 1 g of the organic shrink-preventer is X μmol.

[0043] (fully charged) The fully charged state of a flooded lead-acid battery is defined by JIS D 5301:2019. More specifically, the fully charged state is defined as a state in which the lead-acid battery is charged in a water tank at 25°C ± 2°C with a current (A) 0.2 times the value (unit: Ah) listed as the rated capacity until the terminal voltage (V) during charging or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three consecutive times. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is defined as a state in which constant-current constant-voltage charging of 2.23 V / cell is performed in an air tank at 25°C ± 2°C with a current (A) 0.2 times the value (unit: Ah) listed as the rated capacity, and charging is terminated when the charging current during constant-voltage charging becomes 0.005 times the value (unit: Ah) listed as the rated capacity.

[0044] A fully charged lead-acid battery refers to a lead-acid battery that has already been chemically formed and is fully charged. A lead-acid battery may be fully charged immediately after chemical formation, or after a period of time has passed since chemical formation (for example, a lead-acid battery that has been in use (preferably in the early stages of use) after chemical formation may be fully charged). An early stage battery refers to a battery that has not been in use for very long and has hardly deteriorated at all.

[0045] (Top and bottom directions of lead-acid batteries or components of lead-acid batteries) In this specification, the up-down direction of a lead-acid battery or components of the lead-acid battery (such as plates, a battery case, and a separator) refers to the up-down direction in the vertical direction of the lead-acid battery when the lead-acid battery is in use. Each of the positive and negative plates has a lug for connecting to an external terminal. In some cases, such as a horizontal valve-regulated lead-acid battery, the lug is provided on the side of the plate so as to protrude laterally, but in most lead-acid batteries, the lug is usually provided on the top of the plate so as to protrude upward.

[0046] Hereinafter, the lead-acid battery according to the embodiment of the present invention will be described in detail with respect to each of its main components, but the present invention is not limited to the following embodiment.

[0047] [Lead acid battery] (Negative plate) The negative plate includes a negative current collector and a negative electrode material supported on the negative current collector.

[0048] (Negative electrode current collector) The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the negative electrode current collector because it is easy to support the negative electrode material.

[0049] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed on a part of the negative electrode current collector. The surface layer may be formed on the ear of the negative electrode current collector. The surface layer of the ear may contain Sn or an Sn alloy.

[0050] (Negative electrode material) The negative electrode material includes a polymer compound (P). The negative electrode material further includes a negative electrode active material (specifically, lead or lead sulfate) that exhibits capacity through an oxidation-reduction reaction. The negative electrode material may include at least one selected from the group consisting of carbonaceous materials and other additives. Examples of additives include, but are not limited to, organic shrinkage inhibitors, barium sulfate, and fibers (such as resin fibers). The negative electrode active material in a charged state is sponge-like lead, but an unformed negative plate is usually made using lead powder.

[0051] (Polymer Compound (P)) A first example of the polymer compound (P) is 1 In the chemical shift of the H-NMR spectrum, the peak is in the range of 3.2 ppm to 3.8 ppm. Such a polymer compound (P) is an oxyC 2-4 The oxy C contained in the polymer compound (P) has an alkylene unit. 2-4 Examples of the alkylene unit include an oxyethylene unit, an oxypropylene unit, an oxytrimethylene unit, an oxy2-methyl-1,3-propylene unit, an oxy1,4-butylene unit, and an oxy1,3-butylene unit. The polymer compound (P) contains such an oxyC 2-4 The alkylene unit may have one type or two or more types.

[0052] The polymer compound (P) is oxyC 2-4 It is preferred that the repeating structure of the alkylene unit is a type of oxy C 2-4 It may contain an alkylene unit, and two or more kinds of oxy C 2-4 The polymer compound (P) may contain one type of the repeating structure or two or more types of the repeating structures.

[0053] Oxy C 2-4 The polymer compound (P) having a repeating structure of alkylene units also includes those classified as surfactants (more specifically, nonionic surfactants).

[0054] The polymer compound (P) is, for example, oxy C 2-4 Poly(C) is a hydroxy compound with repeating alkylene units. 2-4 Alkylene glycol, oxy C 2-4 Polyol polyC, a copolymer containing repeating alkylene units 2-4Alkylene oxide adducts, ethers or esters of these hydroxy compounds. 2-4 Examples of alkylene glycols include polyethylene glycol, polypropylene glycol, and polyoxyethylene polyoxypropylene glycol.

[0055] As copolymers, different oxy C 2-4 Copolymers containing alkylene units, etc. The copolymer may be a block copolymer.

[0056] Oxy C 2-4 In a polymer compound (P) containing a repeating structure of an alkylene unit, the proportion of oxy C in all structural units is 2-4 The proportion of the alkylene unit may be in the range of 50 mol% to 100 mol%, 60 mol% to 100 mol% (for example, in the range of 75 mol% to 100 mol%), or 60 mol% to 95 mol% (for example, in the range of 75 mol% to 95 mol%). 2-4 The alkylene units may be oxyethylene units and / or oxypropylene units.

[0057] The polyol may be any of aliphatic polyols, alicyclic polyols, aromatic polyols, and heterocyclic polyols. From the viewpoint of facilitating thin spreading of the polymer compound (P) on the lead surface, aliphatic polyols and alicyclic polyols (e.g., polyhydroxycyclohexane, polyhydroxynorbornane, etc.) are preferred, and among them, aliphatic polyols are preferred. Examples of aliphatic polyols include aliphatic diols and polyols having a triol or more (e.g., glycerin, trimethylolpropane, pentaerythritol, sugar or sugar alcohol, etc.). Examples of aliphatic diols include alkylene glycols having 5 or more carbon atoms. Examples of alkylene glycols include C 5~14 Alkylene glycol or C 5-10The sugar or sugar alcohol may be, for example, sucrose, erythritol, xylitol, mannitol, sorbitol, etc. The sugar or sugar alcohol may be either a chain structure or a cyclic structure. In the polyalkylene oxide adduct of the polyol, the alkylene oxide is the oxy C of the polymer compound (P). 2-4 Corresponding to an alkylene unit, at least C 2-4 It contains an alkylene oxide. From the viewpoint that the polymer compound (P) is likely to have a linear structure, the polyol is preferably a diol.

[0058] The etherified product is the above-mentioned oxy C 2-4 At least some of the terminal -OH groups (composed of a hydrogen atom of the terminal group and an oxygen atom bonded to the hydrogen atom) of the hydroxy compound having a repeating structure of alkylene units are etherified to form -OR 2 Groups, where R 2 is an organic group.) Some or all of the terminals of the polymer compound (P) may be etherified. For example, one terminal of the main chain of the linear polymer compound (P) is an -OH group and the other terminal is an -OR group. 2 It may also be a group.

[0059] The esterified product is the above-mentioned oxy C 2-4 At least some of the terminal -OH groups (composed of a hydrogen atom of the terminal group and an oxygen atom bonded to this hydrogen atom) of a hydroxy compound having a repeating structure of an alkylene unit are esterified to form -OC(=O)-R 3 Groups, where R 3 is an organic group.) Some or all of the terminals of the polymer compound (P) may be esterified. For example, one terminal of the main chain of the linear polymer compound (P) is an -OH group and the other terminal is an -OC(=O)-R 3 It may also be a group.

[0060] organic group R 2and R 3 Each of the above groups includes a hydrocarbon group. The hydrocarbon group may have a substituent (e.g., a hydroxy group, an alkoxy group, and / or a carboxy group). The hydrocarbon group may be any of aliphatic, alicyclic, and aromatic. The aromatic hydrocarbon group and the alicyclic hydrocarbon group may have an aliphatic hydrocarbon group (e.g., an alkyl group, an alkenyl group, an alkynyl group) as a substituent. The number of carbon atoms in the aliphatic hydrocarbon group as a substituent may be, for example, 1 to 30, 1 to 20, 1 to 10, 1 to 6, or 1 to 4.

[0061] Examples of the aromatic hydrocarbon group include aromatic hydrocarbon groups having 24 or less carbon atoms (e.g., 6 to 24). The number of carbon atoms in the aromatic hydrocarbon group may be 20 or less (e.g., 6 to 20), 14 or less (e.g., 6 to 14), or 12 or less (e.g., 6 to 12). Examples of the aromatic hydrocarbon group include aryl groups and bisaryl groups. Examples of the aryl group include phenyl groups and naphthyl groups. Examples of the bisaryl group include monovalent groups corresponding to bisarenes. Examples of bisarenes include biphenyl, bisarylalkanes (e.g., bisC 6-10 Aryl C 1-4 Alkanes (such as 2,2-bisphenylpropane, etc.) are examples.

[0062] Examples of the alicyclic hydrocarbon group include alicyclic hydrocarbon groups having 16 or less carbon atoms. The alicyclic hydrocarbon group may be a cross-linked cyclic hydrocarbon group. The number of carbon atoms in the alicyclic hydrocarbon group may be 10 or less or 8 or less. The number of carbon atoms in the alicyclic hydrocarbon group may be, for example, 5 or more, or 6 or more.

[0063] The alicyclic hydrocarbon group may have 5 (or 6) or more and 16 (or less), 5 (or 6) or more and 10 (or less), or 5 (or 6) or more and 8 (or less) carbon atoms.

[0064] Examples of alicyclic hydrocarbon groups include cycloalkyl groups (cyclopentyl, cyclohexyl, cyclooctyl, etc.), cycloalkenyl groups (cyclohexenyl, cyclooctenyl, etc.), etc. Alicyclic hydrocarbon groups also include hydrogenated products of the above aromatic hydrocarbon groups.

[0065] From the viewpoint of facilitating thin adhesion of the polymer compound (P) to the lead surface, among the hydrocarbon groups, an aliphatic hydrocarbon group is preferred. The aliphatic hydrocarbon group may be saturated or unsaturated. Examples of the aliphatic hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, a dienyl group having two carbon-carbon double bonds, and a trienyl group having three carbon-carbon double bonds. The aliphatic hydrocarbon group may be either linear or branched.

[0066] The number of carbon atoms in the aliphatic hydrocarbon group is, for example, 30 or less, and may be 26 or less or 22 or less, 20 or less or 16 or less, 14 or less or 10 or less, or 8 or less or 6 or less. The lower limit of the number of carbon atoms depends on the type of the aliphatic hydrocarbon group, and is 1 or more for an alkyl group, 2 or more for an alkenyl group and an alkynyl group, 3 or more for a dienyl group, and 4 or more for a trienyl group. Among these, alkyl groups and alkenyl groups are preferred from the viewpoint of facilitating thin adhesion of the polymer compound (P) to the lead surface.

[0067] Specific examples of alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, i-pentyl, s-pentyl, 3-pentyl, t-pentyl, n-hexyl, 2-ethylhexyl, n-octyl, n-nonyl, n-decyl, i-decyl, undecyl, lauryl (dodecyl), tridecyl, myristyl, pentadecyl, cetyl, heptadecyl, stearyl, icosyl, henicosyl, and behenyl.

[0068] Specific examples of the alkenyl group include vinyl, 1-propenyl, allyl, cis-9-heptadecen-1-yl, palmitoleyl, and oleyl. The alkenyl group is, for example, 2-30 Alkenyl group or C 2-26 may be an alkenyl group, C 2-22 Alkenyl group or C 2-20 may be an alkenyl group, C 10-20 It may be an alkenyl group.

[0069] Among the polymer compounds (P), oxy C 2-4 Ethers of hydroxy compounds with repeating alkylene units and oxy C 2-4 It is preferable to use at least one selected from the group consisting of esters of hydroxy compounds having a repeating structure of alkylene units, since this can further enhance the effect of suppressing the decrease in charge acceptance. In addition, the amount of electricity in overcharge can be reduced even when these polymer compounds (P) are used. Among these polymer compounds (P), those having a repeating structure of oxypropylene units or those having a repeating structure of oxyethylene units are preferable.

[0070] The polymer compound (P) may have one or more hydrophobic groups. Examples of the hydrophobic group include, among the above-mentioned hydrocarbon groups, aromatic hydrocarbon groups, alicyclic hydrocarbon groups, and long-chain aliphatic hydrocarbon groups. Examples of the long-chain aliphatic hydrocarbon group include, among the above-mentioned aliphatic hydrocarbon groups (alkyl groups, alkenyl groups, etc.), groups having 8 or more carbon atoms, preferably 12 or more, and more preferably 16 or more. Among them, the polymer compound (P) having a long-chain aliphatic hydrocarbon group is preferable because it is less likely to cause excessive adsorption to lead and further enhances the effect of suppressing the decrease in charge acceptance. The polymer compound (P) may have at least one hydrophobic group that is a long-chain aliphatic hydrocarbon group. The number of carbon atoms of the long-chain aliphatic hydrocarbon group may be 30 or less, 26 or less, or 22 or less.

[0071] The carbon number of the long-chain aliphatic hydrocarbon group may be 8 or more (or 12 or more) and 30 or less, 8 or more (or 12 or more) and 26 or less, 8 or more (or 12 or more) and 22 or less, 10 or more and 30 or less (or 26 or less), or 10 or more and 22 or less.

[0072] Among the polymer compounds (P), those having a hydrophilic group and a hydrophobic group correspond to nonionic surfactants. The repeating structure of the oxyethylene unit exhibits high hydrophilicity and can become the hydrophilic group in the nonionic surfactant. Therefore, it is preferable that the polymer compound (P) having the hydrophobic group contains a repeating structure of the oxyethylene unit. Such a polymer compound (P) can selectively adsorb to lead while suppressing excessive coverage of the lead surface due to the balance between hydrophobicity and high hydrophilicity due to the repeating structure of the oxyethylene unit, so that the effect of suppressing the decrease in charge acceptance can be further enhanced while reducing the amount of overcharge electricity. Such a polymer compound (P) can ensure high adsorption to lead even if it has a relatively low molecular weight (for example, Mn is 1000 or less).

[0073] Among the above polymer compounds (P), polyoxypropylene-polyoxyethylene block copolymers, etherified products of hydroxy compounds having a repeating structure of oxyethylene units, and esterified products of hydroxy compounds having a repeating structure of oxyethylene units correspond to nonionic surfactants.

[0074] Examples of the polymer compound (P) having a hydrophobic group and containing a repeating structure of an oxyethylene unit include etherified polyethylene glycol (such as alkyl ether), esterified polyethylene glycol (such as carboxylate), etherified polyethylene oxide adduct of the above polyol (such as alkyl ether), and esterified polyethylene oxide adduct of the above polyol (such as triol or higher polyol), etc. Specific examples of such polymer compound (P) include polyethylene glycol oleate, polyethylene glycol dioleate, polyethylene glycol dilaurate, polyethylene glycol distearate, polyoxyethylene coconut oil fatty acid sorbitan, polyoxyethylene sorbitan oleate, polyoxyethylene sorbitan stearate, polyoxyethylene lauryl ether, polyoxyethylene tetradecyl ether, polyoxyethylene cetyl ether, etc., but are not limited thereto. Among them, the use of esterified polyethylene glycol, esterified polyethylene oxide adduct of the above polyol, etc. is preferable because it can ensure higher charge acceptance and significantly reduce the amount of overcharge electricity.

[0075] Oxy C is more effective in reducing the amount of overcharged electricity and is easier to secure higher charge acceptance. 2-4 It is also preferable that the repeating structure of alkylene contains at least a repeating structure of an oxypropylene unit. In this case, the charge acceptance tends to be lower than that of a repeating structure of an oxyethylene unit, but even in this case, it is possible to ensure high charge acceptance while suppressing the amount of overcharge electricity to a low level. The polymer compound (P) containing an oxypropylene unit is 1 In the chemical shift of the H-NMR spectrum, peaks derived from -CH< and -CH2- of the oxypropylene unit are present in the range of 3.2 ppm to 3.8 ppm. The peaks are split due to differences in electron density around the nuclei of the hydrogen atoms in these groups. Such a polymer compound (P) has 1In the chemical shift of the H-NMR spectrum, for example, there are peaks in the range of 3.2 ppm to 3.42 ppm and in the range of more than 3.42 ppm to 3.8 ppm. The peak in the range of 3.2 ppm to 3.42 ppm is derived from -CH2-, and the peak in the range of more than 3.42 ppm to 3.8 ppm is derived from -CH< and -CH2-.

[0076] Examples of the polymer compound (P) containing at least a repeating structure of an oxypropylene unit include polypropylene glycol, a copolymer containing a repeating structure of an oxypropylene unit, a polypropylene oxide adduct of the above polyol, or an ether or ester thereof. Examples of the copolymer include an oxypropylene-oxyalkylene copolymer (wherein the oxyalkylene is a C alkylene other than oxypropylene). 2-4 Examples of the oxypropylene-oxyalkylene copolymer include oxypropylene-oxyethylene copolymer and oxypropylene-oxytrimethylene copolymer. The oxypropylene-oxyalkylene copolymer may be called polyoxypropylene-polyoxyalkylene copolymer (for example, polyoxypropylene-polyoxyethylene copolymer). The oxypropylene-oxyalkylene copolymer may be a block copolymer (for example, polyoxypropylene-polyoxyethylene block copolymer). Examples of the etherified product include polypropylene glycol alkyl ether and alkyl ether of oxypropylene-oxyalkylene copolymer (alkyl ether of polyoxypropylene-polyoxyethylene copolymer, etc.). Examples of the esterified product include polypropylene glycol ester of carboxylic acid and carboxylic acid ester of oxypropylene-oxyalkylene copolymer (carboxylic acid ester of polyoxypropylene-polyoxyethylene copolymer, etc.).

[0077] Examples of the polymer compound (P) containing at least a repeating structure of an oxypropylene unit include polypropylene glycol, polyoxypropylene-polyoxyethylene copolymers (polyoxypropylene-polyoxyethylene block copolymers, etc.), polypropylene glycol alkyl ethers (see above R 2 alkyl ethers (methyl ether, ethyl ether, butyl ether, etc.) in which R is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less), polyoxyethylene-polyoxypropylene alkyl ethers (the above R 2 alkyl ethers (butyl ether, hydroxyhexyl ether, etc.) in which R is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less), polypropylene glycol carboxylates (the above R 3 polypropylene glycol carboxylate (polypropylene glycol acetate, etc.) in which the alkyl has 10 or less carbon atoms (or 8 or less or 6 or less), and polypropylene oxide adducts of triol or higher polyols (polypropylene oxide adducts of glycerin, etc.). However, the polymer compound (P) is not limited to these.

[0078] In the polymer compound (P) containing a repeating structure of oxypropylene units, the ratio of oxypropylene units is, for example, 5 mol% or more, and may be 10 mol% or more or 20 mol% or more. The ratio of oxypropylene units is, for example, 100 mol% or less. In the above copolymer, the ratio of oxypropylene units may be 90 mol% or less, 75 mol% or less, 60 mol% or less, or 50 mol% or less, or 43 mol% or less.

[0079] In the polymer compound (P) containing a repeating structure of oxypropylene units, the proportion of the oxypropylene units may be 5 mol% or more and 100 mol% or less (or 90 mol% or less), 10 mol% or more and 100 mol% or less (or 90 mol% or less), 20 mol% or more and 100 mol% or less (or 90 mol% or less), 5 mol% or more and 75 mol% or less (or 60 mol% or less), 10 mol% or more and 75 mol% or less (or 60 mol% or less), 20 mol% or more and 75 mol% or less (or 60 mol% or less), 5 mol% or more and 50 mol% or less (or 43 mol% or less), 10 mol% or more and 50 mol% or less (or 43 mol% or less), or 20 mol% or more and 50 mol% or less (or 43 mol% or less).

[0080] The polymer compound (P) is selected from the group consisting of oxy-C, which is highly adsorbent to lead and can easily assume a linear structure. 2-4 It is preferable that the polymer compound (P) contains a large number of alkylene units. Such a polymer compound (P) contains, for example, an oxygen atom bonded to the terminal group and a -CH2- group and / or a -CH< group bonded to the oxygen atom. 1 In the H-NMR spectrum, the integral value V1 of the peaks between 3.2 ppm and 3.8 ppm is the sum of the integral values ​​of the given peaks V SUM Here, the total integral value of the peak, V SUM is the sum of the integral value V1, the integral value of the peak of the hydrogen atom of the -CH2- group, and the integral value of the peak of the hydrogen atom of the -CH< group. This ratio is, for example, 50% or more, and may be 80% or more. From the viewpoint of further increasing the effect of reducing the overcharge electricity amount and easily ensuring higher charge acceptance, the above ratio is preferably 85% or more, and more preferably 90% or more. For example, when the polymer compound (P) has an -OH group at its terminal and also has a -CH2- group or a -CH< group bonded to the oxygen atom of the -OH group, 1 In the H-NMR spectrum, the peaks of the hydrogen atoms of the -CH2- group and -CH< group have chemical shifts in the range of more than 3.8 ppm to 4.0 ppm.

[0081] The negative electrode material may contain one type of polymer compound (P) or two or more types of polymer compounds (P).

[0082] The polymer compound (P) may include, for example, a compound with Mn of 5 million or less, a compound with Mn of 3 million or less or 2 million or less, a compound with Mn of 500,000 or less or 100,000 or less, or a compound with Mn of 50,000 or less or 20,000 or less. From the viewpoint of ensuring higher charge acceptance, the polymer compound (P) preferably includes a compound with Mn of 10,000 or less, a compound with Mn of 5,000 or less or 4,000 or less, or a compound with Mn of 3,000 or less or 2,500 or less. The Mn of such a compound may be 300 or more or 400 or more, or may be 500 or more. From the viewpoint of further enhancing the effect of reducing the overcharged amount of electricity, the Mn of such a compound is preferably 1,000 or more, more preferably 1,500 or more or 1,800 or more. As the polymer compound (P), two or more compounds with different Mn may be used. That is, the polymer compound (P) may have a plurality of Mn peaks in the molecular weight distribution.

[0083] The Mn of the above compounds is 300 or more (or 400 or more) and 5 million or less, 300 or more (or 400 or more) and 3 million or less, 300 or more (or 400 or more) and 2 million or less, 300 or more (or 400 or more) and 500,000 or less, 300 or more (or 400 or more) and 100,000 or less, 300 or more (or 400 or more) and 50,000 or less, 300 or more (or 400 or more) and 20,000 or less, 300 or more (or 400 or more) and 10,000 or less, 300 or more (or 400 or more) and 5,000 or less, 300 or more (or 400 or more) 4000 or less, 300 or more (or 400 or more) 3000 or less, 300 or more (or 400 or more) 2500 or less, 500 or more (or 1000 or more) 5 million or less, 500 or more (or 1000 or more) 3 million or less, 500 or more (or 1000 or more) 2 million or less, 500 or more (or 1000 or more) 500,000 or less, 500 or more (or 1000 or more) 100,000 or less, 500 or more (or 1000 or more) 50,000 or less, 500 or more (or 1000 or more) 20,000 or less, 500 or more (or 1,000 or more) 10,000 or less, 500 or more (or 1,000 or more) 5,000 or less, 500 or more (or 1,000 or more) 4,000 or less, 500 or more (or 1,000 or more) 3,000 or less, 500 or more (or 1,000 or more) 2,500 or less, 1,500 or more (or 1,800 or more) 5 million or less, 1,500 or more (or 1,800 or more) 3 million or less, 1,500 or more (or 1,800 or more) 2 million or less, 1,500 or more (or 1,800 or more) but not exceeding 500,000, 1,500 or more (or 1,800 or more) but not exceeding 100,000, 1,500 or more (or 1,800 or more) but not exceeding 50,000, 1,500 or more (or 1,800 or more) but not exceeding 20,000, 1,500 or more (or 1,800 or more) but not exceeding 10,000, 1,500 or more (or 1,800 or more) but not exceeding 5,000, 1,500 or more (or 1,800 or more) but not exceeding 4,000, 1,500 or more (or 1,800 or more) but not exceeding 3,000, or 1,500 or more (or 1,800 or more) but not exceeding 2,500.

[0084] The content of the polymer compound (P) in the entire negative electrode material is, for example, 8 ppm or more, and may be 10 ppm or more, based on mass. From the viewpoint of further enhancing the effect of reducing the amount of overcharge electricity, the content of the polymer compound (P) in the entire negative electrode material is, for example, 20 ppm or more, and more preferably 30 ppm or more, based on mass. The content of the polymer compound (P) in the entire negative electrode material is, for example, 1000 ppm or less, and may be less than 1000 ppm, 700 ppm or less, 600 ppm or less, or 500 ppm or less, based on mass. From the viewpoint of easily ensuring higher charge acceptance, the content of the polymer compound (P) in the entire negative electrode material is, for example, 400 ppm or less, more preferably 300 ppm or less, and may be 200 ppm or less or 160 ppm or less, 150 ppm or less or 120 ppm or less, or may be 100 ppm or less, based on mass.

[0085] The content (by mass) of polymer compounds (P) in the entire negative electrode material is 8 ppm or more (or 10 ppm or more) and 1000 ppm or less, 8 ppm or more (or 10 ppm or more) and less than 1000 ppm, 8 ppm or more (or 10 ppm or more) and 700 ppm or less, 8 ppm or more (or 10 ppm or more) and 600 ppm or less, 8 ppm or more (or 10 ppm or more) and 500 ppm or less, 8 ppm or more (or 10 ppm or more) and 400 ppm or less, 8 ppm or more (or 10 ppm or more) and 300 ppm or less, 8 ppm or more (or 10 ppm or more) and 200 ppm or less, 8 ppm or more (or 10 ppm or more) and 160 ppm or less, 8 ppm or more (or 10 ppm or more) and 150 ppm or less, 8 ppm or more (or 10 ppm or more) and 120 ppm or less, 8 ppm or more (or 10 ppm or more) and 10 0ppm or less, 20ppm or more (or 30ppm or more) 1000ppm or less, 20ppm or more (or 30ppm or more) less than 1000ppm, 20ppm or more (or 30ppm or more) 700ppm or less, 20ppm or more (or 30ppm or more) 600ppm or less, 20ppm or more (or 30ppm or more) 500ppm or less, 20ppm or more (or 30ppm or more) 400ppm or less, 2 It may be 0 ppm or more (or 30 ppm or more) to 300 ppm or less, 20 ppm or more (or 30 ppm or more) to 200 ppm or less, 20 ppm or more (or 30 ppm or more) to 160 ppm or less, 20 ppm or more (or 30 ppm or more) to 150 ppm or less, 20 ppm or more (or 30 ppm or more) to 120 ppm or less, or 20 ppm or more (or 30 ppm or more) to 100 ppm or less.

[0086] (Organic shrink-proofing agent) Organic shrink-proofing agents are generally classified into lignin compounds and synthetic organic shrink-proofing agents. Synthetic organic shrink-proofing agents can also be said to be organic shrink-proofing agents other than lignin compounds. Examples of organic shrink-proofing agents contained in the negative electrode material include lignin compounds and synthetic organic shrink-proofing agents. The negative electrode material may contain one type of organic shrink-proofing agent or two or more types of organic shrink-proofing agents. The organic shrink-proofing agent may be a known organic shrink-proofing agent used in lead-acid batteries.

[0087] Examples of the lignin compound include lignin and lignin derivatives. Examples of the lignin derivatives include lignin sulfonic acid or salts thereof (alkali metal salts (sodium salts, etc.)).

[0088] The synthetic organic shrink-proofing agent is an organic polymer containing elemental sulfur, and generally contains multiple aromatic rings in the molecule and elemental sulfur as a sulfur-containing group. Among the sulfur-containing groups, sulfonic acid groups or sulfonyl groups, which are stable, are preferred. The sulfonic acid groups may exist in the acid form or in the salt form such as Na salt.

[0089] The organic shrinkage inhibitor may be a condensation product containing at least an aromatic compound unit. Examples of such condensation products include condensation products of aromatic compounds with aldehyde compounds (at least one selected from the group consisting of aldehydes (e.g., formaldehyde) and condensates thereof). The organic shrinkage inhibitor may contain one type of aromatic compound unit, or may contain two or more types of aromatic compound units. The aromatic compound unit refers to a unit derived from an aromatic compound incorporated in the condensation product. Preferred aromatic compounds include bisphenol A, bisphenol S, and bisphenol F.

[0090] The negative electrode material may contain, for example, an organic shrink-proofing agent (first organic shrink-proofing agent) having a sulfur element content of 2000 μmol / g or more among the above organic shrink-proofing agents. Examples of the first organic shrink-proofing agent include the above synthetic organic shrink-proofing agents (such as the above condensates).

[0091] The sulfur element content of the first organic shrinkage inhibitor may be 2000 μmol / g or more, and preferably 3000 μmol / g or more. The upper limit of the sulfur element content of the organic shrinkage inhibitor is not particularly limited, but from the viewpoint of further enhancing the effect of reducing the amount of overcharge electricity, it is preferably 9000 μmol / g or less, and more preferably 8000 μmol / g or less.

[0092] The sulfur element content of the first organic shrink inhibitor may be, for example, 2000 μmol / g or more (or 3000 μmol / g or more) and 9000 μmol / g or less, or 2000 μmol / g or more (or 3000 μmol / g or more) and 8000 μmol / g or less.

[0093] The first organic shrinkage inhibitor includes a condensate containing a unit of an aromatic compound having a sulfur-containing group, and the condensate may contain at least a unit of a bisphenol compound as the unit of the aromatic compound.

[0094] The weight average molecular weight (Mw) of the first organic shrink-proofing agent is preferably equal to or greater than 7000. The Mw of the first organic shrink-proofing agent is, for example, equal to or less than 100,000, and may be equal to or less than 20,000.

[0095] The negative electrode material may contain, for example, an organic shrink-proofing agent (second organic shrink-proofing agent) having a sulfur element content of less than 2000 μmol / g. The second organic shrink-proofing agent may be, among the above organic shrink-proofing agents, a lignin compound, a synthetic organic shrink-proofing agent (particularly, a lignin compound), or the like. The sulfur element content of the second organic shrink-proofing agent is preferably 1000 μmol / g or less, and may be 800 μmol / g or less. The lower limit of the sulfur element content in the second organic shrink-proofing agent is not particularly limited, but is, for example, 400 μmol / g or more.

[0096] The Mw of the second organic shrink-proofing agent is, for example, less than 7000. The Mw of the second organic shrink-proofing agent is, for example, 3000 or more.

[0097] The negative electrode material may contain a second organic shrink-proofing agent in addition to the first organic shrink-proofing agent. When the first organic shrink-proofing agent and the second organic shrink-proofing agent are used in combination, the mass ratio thereof can be selected arbitrarily.

[0098] The content of the organic shrinkage inhibitor contained in the negative electrode material is, for example, 0.005% by mass or more, and may be 0.01% by mass or more. When the content of the organic shrinkage inhibitor is in such a range, a high low-temperature high-rate discharge capacity can be ensured. The content of the organic shrinkage inhibitor is, for example, 1.0% by mass or less, and may be 0.5% by mass or less. From the viewpoint of further enhancing the effect of suppressing the decrease in charge acceptance, the content of the organic shrinkage inhibitor is preferably 0.3% by mass or less, more preferably 0.25% by mass or less, further preferably 0.2% by mass or less or 0.15% by mass or less, and may be 0.12% by mass or less.

[0099] The content of the organic shrinkage preventer in the negative electrode material may be 0.005% by mass or more (or 0.01% by mass or more) to 1.0% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) to 0.5% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) to 0.3% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) to 0.25% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) to 0.2% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) to 0.15% by mass or less, or 0.005% by mass or more (or 0.01% by mass or more) to 0.12% by mass or less.

[0100] (carbonaceous material) Carbon black, graphite, hard carbon, soft carbon, etc. can be used as the carbonaceous material contained in the negative electrode material. Examples of carbon black include acetylene black, furnace black, lamp black, etc. Furnace black also includes Ketjen Black (trade name). Graphite may be any carbonaceous material containing a graphite-type crystal structure, and may be either artificial graphite or natural graphite. The negative electrode material may contain one type of carbonaceous material, or may contain two or more types.

[0101] The content of the carbonaceous material in the negative electrode material is, for example, 0.05 mass% or more, and may be 0.10 mass% or more.The content of the carbonaceous material is, for example, 5 mass% or less, and may be 3 mass% or less.

[0102] The content of the carbonaceous material in the negative electrode material may be 0.05% by mass to 5% by mass, 0.05% by mass to 3% by mass, 0.10% by mass to 5% by mass, or 0.10% by mass to 3% by mass.

[0103] (Barium Sulfate) The content of barium sulfate in the negative electrode material is, for example, 0.05% by mass or more, and may be 0.10% by mass or more. The content of barium sulfate in the negative electrode material is, for example, 3% by mass or less, and may be 2% by mass or less.

[0104] The content of barium sulfate in the negative electrode material may be from 0.05 to 3% by mass, from 0.05 to 2% by mass, from 0.10 to 3% by mass, or from 0.10 to 2% by mass.

[0105] (Analysis of negative electrode materials or components) The following describes a method for analyzing the negative electrode material or its constituents. Prior to measurement or analysis, a fully charged lead-acid battery is disassembled to obtain a negative electrode plate to be analyzed. The obtained negative electrode plate is washed with water to remove sulfuric acid from the negative electrode plate. The washing is performed by pressing a pH test paper against the washed surface of the negative electrode plate until it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative electrode plate is dried at 60±5°C for about 6 hours under a reduced pressure environment. If the negative electrode plate contains an attachment material, the attachment material is removed as necessary. Next, a sample (hereinafter referred to as sample A) is obtained by separating the negative electrode material from the negative electrode plate. Sample A is crushed as necessary and subjected to analysis. When the content of the polymer compound (P) in a specific part in the thickness direction of the negative electrode plate is measured, a material for measurement may be obtained from that part.

[0106] (1) Analysis of polymer compounds (P) (1-1) Qualitative analysis of polymer compounds (P) A crushed sample A is used. 150.0±0.1 mL of chloroform is added to 100.0±0.1 g of sample A, and the mixture is stirred at 20±5°C for 16 hours to extract the polymer compound (P). The solid content is then removed by filtration. The polymer compound (P) obtained by extraction is dissolved in a chloroform solution or by drying the chloroform solution, and information is obtained from at least one of infrared spectroscopy, ultraviolet-visible absorption spectroscopy, NMR spectroscopy, LC-MS, and pyrolysis GC-MS to identify the polymer compound (P).

[0107] From the chloroform solution in which the polymer compound (P) obtained by extraction is dissolved, chloroform is distilled off under reduced pressure to recover the chloroform-soluble matter. The chloroform-soluble matter is dissolved in deuterated chloroform and then stirred under the following conditions: 1 1H-NMR spectrum is measured. 1 From the H-NMR spectrum, a peak with a chemical shift in the range of 3.2 ppm to 3.8 ppm is confirmed. Also, from the peak in this range, oxy C 2-4 Identify the type of alkylene unit.

[0108] Apparatus: AL400 nuclear magnetic resonance spectrometer manufactured by JEOL Ltd. Observation frequency: 395.88MHz Pulse width: 6.30μs Pulse repetition time: 74.1411 seconds Accumulation count: 32 Measurement temperature: room temperature (20~35℃) Standard: 7.24 ppm Sample tube diameter: 5mm

[0109] 1 From the H-NMR spectrum, the integral value (V1) of the peaks present in the chemical shift range of 3.2 ppm to 3.8 ppm is determined. In addition, for each of the hydrogen atoms of the -CH2- group and -CH< group bonded to the oxygen atom bonded to the terminal group of the polymer compound (P), 1The sum (V2) of the integral values ​​of the peaks in the H-NMR spectrum is calculated. Then, from V1 and V2, the percentage of V1 in the sum of V1 and V2 (=V1 / (V1+V2)×100(%)) is calculated.

[0110] In addition, in the qualitative analysis, 1 When calculating the integral value of a peak in a H-NMR spectrum, 1 In the H-NMR spectrum, two points without significant signals are determined so as to sandwich the corresponding peak, and each integral value is calculated using a straight line connecting these two points as a baseline. For example, for a peak that exists in a chemical shift range of 3.2 ppm to 3.8 ppm, a straight line connecting two points on the spectrum between 3.2 ppm and 3.8 ppm is used as the baseline. For example, for a peak that exists in a chemical shift range of more than 3.8 ppm to 4.0 ppm, a straight line connecting two points on the spectrum between 3.8 ppm and 4.0 ppm is used as the baseline.

[0111] (1-2) Quantitative analysis of polymer compounds (P) The appropriate amount of the chloroform soluble matter was measured with an accuracy of ±0.0001 g. r (g) Dissolve in deuterated chloroform together with tetrachloroethane (TCE), 1 Measure the H-NMR spectrum. The integral value (S a ) and the integral value of the peak due to TCE (S r ) and calculate the mass-based content C of the polymer compound (P) in the negative electrode material from the following formula: n Calculate the ppm.

[0112] C n =S a / S r ×N r / N a ×M a / M r ×m r / m×1000000 (In the formula, M aThe molecular weight of the structure that shows a peak in the chemical shift range of 3.2 to 3.8 ppm (more specifically, oxy C 2-4 (the molecular weight of the repeating structure of alkylene units) and N a is the number of hydrogen atoms attached to the carbon atoms in the main chain of the repeating unit. r、 M r are the number of hydrogen atoms contained in the molecule of the reference material, the molecular weight of the reference material, and m (g) is the mass of the negative electrode material used for extraction.) In addition, the standard substance in this analysis is TCE, so N r =2, M r = 168. Also, m = 100.

[0113] For example, when the polymer compound (P) is polypropylene glycol, M a is 58, and N a is 3. When the polymer compound (P) is polyethylene glycol, M a is 44, and N a is 4. N a and M. a is the N of each monomer unit a Value and M a The value is calculated by averaging the molar ratio (mol %) of each monomer unit contained in the repeating structure.

[0114] In addition, in the quantitative analysis, 1 The integral value of the peak in the H-NMR spectrum is determined using data processing software “ALICE” manufactured by JEOL Ltd.

[0115] (1-3) Mn measurement of polymer compound (P) Using the above chloroform solubles, GPC measurement of polymer compound (P) is performed using the following apparatus under the following conditions. Separately, a calibration curve (calibration curve) is created from a plot of Mn of the standard substance versus elution time. Based on this calibration curve and the GPC measurement results of polymer compound (P), Mn of polymer compound (P) is calculated. However, esterified or etherified products may be in a decomposed state in the chloroform solubles.

[0116] Analysis system: 20A system (Shimadzu Corporation) Column: Two GPC KF-805L (Shodex) columns connected in series Column temperature: 30℃±1℃ Mobile phase: Tetrahydrofuran Flow rate: 1mL / min. Concentration: 0.20% by mass Injection volume: 10μL Standard substance: polyethylene glycol (Mn=2,000,000, 200,000, 20,000, 2,000, 200) Detector: Differential refractive index detector (Shodex RI-201H)

[0117] (others) The negative electrode plate can be formed by applying or filling a negative electrode paste onto a negative electrode current collector, aging and drying to prepare an unformed negative electrode plate, and then chemically forming the unformed negative electrode plate. The negative electrode paste is prepared, for example, by adding water and sulfuric acid (or an aqueous sulfuric acid solution) to lead powder, a polymer compound (P), and, if necessary, at least one selected from the group consisting of an organic shrinkage inhibitor, a carbonaceous material, and other additives, and kneading the mixture. When aging, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at a high humidity.

[0118] The formation can be carried out by immersing the plate group including the unformed negative plate in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the plate group. However, the formation may be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.

[0119] (Positive plate) The positive electrode plate of the lead-acid battery can be classified into a paste type, a clad type, and the like. Either a paste type or a clad type positive electrode plate may be used. The paste type positive electrode plate includes a positive electrode current collector and a positive electrode material. The configuration of the clad type positive electrode plate is as described above.

[0120] The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.

[0121] As the lead alloy used for the positive electrode current collector, in terms of corrosion resistance and mechanical strength, Pb-Sb alloy, Pb-Ca alloy, Pb-Ca-Sn alloy are preferable. The positive electrode current collector may have a surface layer. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the lattice part, only on the edge part, or only on the frame part of the positive electrode current collector.

[0122] The positive electrode material contained in the positive electrode plate contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.

[0123] The unformed paste-type positive plate is obtained by filling a positive current collector with a positive electrode paste, aging and drying. The positive electrode paste is prepared by kneading lead powder, additives, water and sulfuric acid. The unformed clad-type positive plate is formed by filling a porous tube into which a core metal connected by a current collector is inserted with lead powder or lead powder in a slurry form, and connecting a plurality of tubes with a connecting member. Then, the unformed positive plate is formed to obtain a positive plate. The formation can be performed by charging the plate group in a state where the plate group including the unformed positive plate is immersed in an electrolyte containing sulfuric acid in a battery container of a lead-acid battery. However, the formation may be performed before assembling the lead-acid battery or the plate group.

[0124] The formation can be carried out by immersing an electrode plate group including unformed positive plates in an electrolyte solution containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group, although the formation may also be carried out before assembling the lead-acid battery or the electrode plate group.

[0125] (Separator) A separator may be disposed between the negative electrode plate and the positive electrode plate, and may be made of at least one material selected from a nonwoven fabric and a microporous membrane.

[0126] A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% or more by mass of the nonwoven fabric is made of fibers. As the fibers, glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (polyethylene terephthalate fibers, etc.), pulp fibers, etc.) can be used. Among them, glass fibers are preferable. The nonwoven fabric may contain components other than fibers, such as acid-resistant inorganic powders and polymers as binders.

[0127] On the other hand, a microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and is preferably made mainly of a polymer component. The polymer component is preferably polyolefin (polyethylene, polypropylene, etc.). The pore-forming agent can be at least one selected from the group consisting of polymer powder and oil.

[0128] The separator may be, for example, composed of only a nonwoven fabric or only a microporous membrane. Furthermore, the separator may be, as necessary, a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same materials, or a laminate of different or the same materials with recesses and projections interlocked.

[0129] The separator may be in a sheet shape or may be formed in a bag shape. A sheet-shaped separator may be sandwiched between the positive electrode plate and the negative electrode plate. Also, the electrode plate may be sandwiched between a folded sheet-shaped separator. In this case, the positive electrode plate sandwiched between the folded sheet-shaped separator and the negative electrode plate sandwiched between the folded sheet-shaped separator may be stacked, or one of the positive electrode plate and the negative electrode plate may be sandwiched between the folded sheet-shaped separator and stacked with the other electrode plate. Also, the sheet-shaped separator may be folded into an accordion shape, and the positive electrode plate and the negative electrode plate may be sandwiched between the accordion-shaped separator so that the separator is interposed between them. When a bag-shaped separator is used, the bag-shaped separator may house the positive electrode plate or the negative electrode plate.

[0130] (electrolyte) The electrolytic solution is an aqueous solution containing sulfuric acid, which may be gelled as necessary. The electrolytic solution may contain the above-mentioned polymer compound (P).

[0131] The electrolytic solution may contain cations (e.g., metal cations) and / or anions (e.g., anions other than sulfate anions (e.g., phosphate ions)) as necessary. Examples of metal cations include at least one selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.

[0132] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. is, for example, 1.20 or more, and may be 1.25 or more. The specific gravity of the electrolyte at 20° C. is 1.35 or less, and preferably 1.32 or less.

[0133] The specific gravity of the electrolyte at 20° C. may be 1.20 or more and 1.35 or less, 1.20 or more and 1.32 or less, 1.25 or more and 1.35 or less, or 1.25 or more and 1.32 or less.

[0134] (others) The lead-acid battery can be obtained by a manufacturing method including a step of housing a plate group and an electrolyte in a cell chamber of a battery case. Each cell of the lead-acid battery includes a plate group and an electrolyte housed in each cell chamber. The plate group is assembled by stacking a positive electrode plate, a negative electrode plate, and a separator such that the separator is interposed between the positive electrode plate and the negative electrode plate prior to housing in the cell chamber. The positive electrode plate, the negative electrode plate, the electrolyte, and the separator are each prepared prior to assembling the plate group. The manufacturing method of the lead-acid battery may include a step of chemically forming at least one of the positive electrode plate and the negative electrode plate, as necessary, after the step of housing the plate group and the electrolyte in the cell chamber.

[0135] The number of plates in the plate group may be one or more. From the viewpoint of ensuring a high effect of reducing the amount of overcharge electricity, it is preferable that 50% or more (more preferably 80% or more or 90% or more) of the number of negative plates included in the plate group satisfy the above condition. The ratio of the negative plates included in the plate group that satisfy the above condition is 100% or less. All of the negative plates included in the plate group may satisfy the above condition.

[0136] When a lead-acid battery has two or more cells, it is sufficient that the plate groups of at least some of the cells include negative plates that satisfy the above conditions. From the viewpoint of ensuring a high effect of reducing the amount of overcharge electricity, it is preferable that 50% or more (more preferably 80% or more or 90% or more) of the number of cells included in the lead-acid battery include plate groups including negative plates that satisfy the above conditions. The ratio of cells included in the lead-acid battery that include plate groups including negative plates that satisfy the above conditions is 100% or less. It is preferable that all of the plate groups included in the lead-acid battery include negative plates that satisfy the above conditions.

[0137] An example of a lead-acid battery according to an embodiment of the present invention will be described below with reference to the drawings. The above description can be applied to the embodiment described below. The embodiment described below may be modified based on the above description. The matters described below may be applied to the above embodiment. Among the matters described below, matters that are not essential to the present invention may be omitted.

[0138] FIG. 1 shows an external view of an example of a lead-acid battery according to an embodiment of the present invention. The lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The inside of the battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one plate group 11. The opening of the battery case 12 is closed by a lid 15 that includes a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When rehydrating, the vent plug 18 is removed and rehydration liquid is replenished. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.

[0139] Each electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with a separator 4 interposed therebetween. Here, a pouch-shaped separator 4 that accommodates the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In a cell chamber 14 located at one end of the battery case 12, a negative electrode shelf portion 6 that connects a plurality of negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode shelf portion 5 that connects a plurality of positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 outside the lid 15. In a cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf portion 6, and a through connector 8 is connected to the positive electrode shelf portion 5. The negative electrode column 9 is connected to a negative electrode terminal 16 outside the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13 to connect the electrode plate groups 11 of adjacent cell chambers 14 in series.

[0140] The positive electrode shelf 5 is formed by welding the lugs provided on the upper part of each positive electrode plate 3 together by a cast-on-strap method or a burning method. The negative electrode shelf 6 is also formed by welding the lugs provided on the upper part of each negative electrode plate 2 together in the same manner as the positive electrode shelf 5.

[0141] The lid 15 of the lead-acid battery has a single structure (single lid), but is not limited to the illustrated example. The lid 15 may have a double structure including, for example, an inner lid and an outer lid (or a top lid). The lid having a double structure may have a reflux structure between the inner lid and the outer lid for returning the electrolyte to the inside of the battery (inside the inner lid) from a reflux port provided in the inner lid.

[0142] FIG. 2A is a schematic cross-sectional view of a portion of an example of a negative electrode plate 2. FIG. 2B is a schematic cross-sectional view taken along line IIB-IIB in FIG. 2A. The cross-sectional view in FIG. 2A is a cross-sectional view taken along line IIA-IIA in FIG. 2B. Note that FIGS. 2A and 2B are schematic views and are different from actual views. For example, when the negative electrode current collector 2a is an expanded lattice, the cross-sectional view may not be as shown in FIGS. 2A and 2B.

[0143] The negative electrode plate 2 includes a lattice-shaped negative electrode collector 2a and a negative electrode material 2b supported by the negative electrode collector 2a. The negative electrode collector 2a includes a lattice portion composed of a plurality of linear portions 2aa. The negative electrode material 2b includes a first negative electrode material (first layer portion) 2b1 and a second negative electrode material 2b2 (second layer portion). The first negative electrode material 2b1 is disposed in the gaps (gap of the lattice portion) between the plurality of linear portions 2aa and is in contact with the negative electrode collector 2a. In the example shown in FIG. 2A, the first negative electrode material (first layer portion) 2b1 is sandwiched between two second layer portions (second negative electrode material 2b2) disposed on the outside thereof. That is, in the example shown in FIG. 2A, two second layer portions (second negative electrode material 2b2) are arranged to sandwich the first layer portion (first negative electrode material 2b1) and the negative electrode current collector 2a.

[0144] In addition, FIG. 2B shows an example in which the boundary between the first negative electrode material 2b1 and the second negative electrode material 2b2 is clear. However, the boundary between them does not have to be clear. For example, the content of the polymer compound (P) may gradually decrease from the center of the negative electrode plate 2 in the thickness direction toward the surface side of the negative electrode plate 2.

[0145] In one example, as shown in FIG. 3, it is also possible to divide the negative electrode material 2b arranged on the negative electrode plate 2 into three regions in the thickness direction. In FIG. 3, the negative electrode material 2b is divided in the thickness direction into a first region 2ba in the center and two second regions 2bb on both sides of the first region 2ba. In this example, the thicknesses of the two second regions 2bb are equal, but they may be different. In this example, the content of the polymer compound (P) in the first region 2ba in the center is greater than the content of the polymer compound (P) in the two second regions 2bb on both sides of the first region 2ba. The negative electrode material constituting the first region 2ba is the first negative electrode material in contact with the negative electrode collector 2a. The negative electrode material constituting the second region 2bb is the second negative electrode material arranged outside the first negative electrode material. When the thickness of the negative electrode material 2b arranged on the negative electrode plate 2 is T, the thickness T1 of the first region 2ba and the thickness T2 of one second region 2bb may be in the above-mentioned range.

[0146] The two boundaries between the first region 2ba and the second region 2bb may coincide with the surfaces S1 and S2 on both sides of the negative electrode current collector 2a, respectively. Here, the surface S1 is equal to the surface of a metal plate (e.g., 1 mm thick) made of the same material as the negative electrode current collector 2a when pressed against the negative electrode current collector 2a. The distance between the surfaces S1 and S2 can be regarded as the thickness of the negative electrode current collector 2a.

[0147] 2B and 3 illustrate the case where the second negative electrode material is disposed on the outside of the two main surfaces of the first negative electrode material. However, the second negative electrode material may be disposed only on the outside of one main surface of the first negative electrode material. That is, one of the two layered second negative electrode materials shown in FIG. 2B and FIG. 3 may be omitted. However, the effect obtained is higher when the two layered second negative electrode material is used.

[0148] There is no particular limitation on the method of manufacturing the negative electrode plate 2 as shown in FIG. 2A, FIG. 2B, and FIG. 3. The first and second examples of the manufacturing method will be described below. In the first example, a negative electrode plate is manufactured using negative electrode pastes with different contents of the polymer compound (P). Specifically, first, a first negative electrode paste containing the polymer compound (P) and a second negative electrode paste with a lower content of the polymer compound (P) than the first negative electrode paste are prepared. Next, the first negative electrode paste is applied to the negative electrode current collector so that the voids in the negative electrode current collector are filled with the first negative electrode paste. Next, the second negative electrode paste is applied to both sides of the negative electrode current collector and the first negative electrode paste so as to sandwich them. Thereafter, a process such as drying is performed as necessary. In this manner, the negative electrode plate 2 can be manufactured.

[0149] By changing the content of the polymer compound (P) in the first negative electrode paste and the content of the polymer compound (P) in the second negative electrode paste, the content of the polymer compound (P) in the first negative electrode material, the content of the polymer compound in the second negative electrode material, and the ratio thereof can be changed.

[0150] In the second example, first and second negative electrode pastes are prepared. Each of the first and second negative electrode pastes may or may not contain a polymer compound (P). Next, the first negative electrode paste is applied to the negative electrode current collector so that the voids in the negative electrode current collector are filled with the first negative electrode paste. Next, the applied first negative electrode paste is dried to form a first electrode material layer. Next, the first electrode material layer is contacted with a liquid containing the polymer compound (P). This increases the content of the polymer compound (P) in the first electrode material layer. For example, the first electrode material layer may be immersed in a liquid containing the polymer compound (P). Alternatively, the first electrode material layer may be sprayed with a liquid containing the polymer compound (P). The content of the polymer compound (P) in the finally obtained first negative electrode material can be changed depending on the concentration of the polymer compound (P) in the liquid and the contact time. Next, the second negative electrode paste is applied to both sides of the negative electrode current collector and the first electrode material layer so as to sandwich them. After that, a process such as drying is performed as necessary. In this manner, the negative electrode plate 2 can be manufactured. In the second example, the magnitude relationship between the content of the polymer (P) in the first negative electrode paste and the content of the polymer compound (P) in the second negative electrode paste is not limited. Ultimately, it is sufficient that the above-mentioned negative electrode plate is manufactured. Note that, between the application of the first negative electrode paste and the application of the second negative electrode paste, a step of drying the first negative electrode paste may or may not be performed.

[0151] A lead-acid battery according to one aspect of the present invention will be described below.

[0152] (1) A lead-acid battery, A positive electrode plate and a negative electrode plate are included. The negative electrode plate includes a negative electrode current collector and a negative electrode material supported on the negative electrode current collector, the negative electrode material includes a first negative electrode material in contact with the negative electrode current collector and a second negative electrode material disposed outside the first negative electrode material, The content (ppm) of the polymer compound in the first negative electrode material is greater than the content (ppm) of the polymer compound in the second negative electrode material; The polymer compound is measured using deuterated chloroform as a solvent. 1 A lead-acid battery having a peak in the range of 3.2 ppm or more and 3.8 ppm or less in the chemical shift of the H-NMR spectrum.

[0153] (2) A lead-acid battery, A positive electrode plate and a negative electrode plate are included. The negative electrode plate includes a negative electrode current collector and a negative electrode material supported on the negative electrode current collector, the negative electrode material includes a first negative electrode material in contact with the negative electrode current collector and a second negative electrode material disposed outside the first negative electrode material, The content (ppm) of the polymer compound in the first negative electrode material is greater than the content (ppm) of the polymer compound in the second negative electrode material; The polymer compound is oxyC 2-4 A lead-acid battery comprising a repeating structure of alkylene units.

[0154] (3) In the lead-acid battery according to (2), the polymer compound is 2-4 The hydroxy compound may contain at least one selected from the group consisting of a hydroxy compound containing the repeating structure of an alkylene unit, an etherified product of the hydroxy compound, and an esterified product of the hydroxy compound.

[0155] (4) In the lead-acid battery described above in (2), the polymer compound may include an ester of a polyalkylene glycol having an alkylene group with 2 to 4 carbon atoms.

[0156] (5) In the lead-acid battery according to any one of the above (1) to (4), the negative electrode current collector may include a plurality of linear portions. In this case, the first negative electrode material may be disposed in gaps between the plurality of linear portions.

[0157] (6) In the lead-acid battery described above in (5), the negative electrode current collector may have a lattice portion constituted by the plurality of linear portions.

[0158] (7) In the lead-acid batteries according to any one of (1) to (6) above, the content (ppm) of the polymer compound in the second negative electrode material may be in the range of 0 to 0.7 times the content (ppm) of the polymer compound in the first negative electrode material.

[0159] (8) In the lead-acid batteries according to any one of (1) to (7) above, the content by mass of the polymer compound in the first negative electrode material may be in the range of 80 ppm to 500 ppm.

[0160] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0161] 《Lead acid batteries A1~A6, C1~C6, R1》 (1) Preparation of lead-acid batteries (a) Preparation of the negative electrode plate The raw materials lead powder, barium sulfate, carbon black, an organic shrinkage preventer (sodium lignin sulfonate), and optionally a polymer compound (P) are mixed with an appropriate amount of sulfuric acid aqueous solution to obtain a first negative electrode paste. The polymer compound (P) is added to the first negative electrode paste so that the content (by mass) of the polymer compound (P) in the first negative electrode material is the content in Table 1. Similarly, each component is mixed so that the content of the organic shrinkage preventer, the content of the barium sulfate, and the content of the carbon black in the first negative electrode material are 0.1 mass%, 0.4 mass%, and 0.2 mass%, respectively. Sodium lignin sulfonate is used as the organic shrinkage preventer.

[0162] Next, the second negative electrode paste is prepared in the same manner as the first negative electrode paste, except that the polymer compound (P) is added so that the content (by mass) of the polymer compound (P) in the second negative electrode material is the content in Table 1. Next, the first negative electrode paste is applied to the negative electrode current collector so that the first negative electrode paste is filled in the gaps in the lattice part of the negative electrode current collector. For the negative electrode current collector, a negative electrode current collector including an expanded lattice made of a Pb-Ca-Sn alloy is used. Next, the second negative electrode paste is applied to both sides of the expanded lattice and the first negative electrode paste supported by it so as to sandwich them. Next, the obtained electrode is aged and dried to obtain an unformed negative electrode plate. The first negative electrode paste becomes the first negative electrode material, and the second negative electrode paste becomes the second negative electrode material.

[0163] (b) Preparation of the positive electrode plate The raw lead powder is mixed with an aqueous sulfuric acid solution to obtain a positive electrode paste, which is then filled into the mesh of an expanded lattice made of a Pb-Ca-Sn alloy, aged and dried to obtain an unformed positive electrode plate.

[0164] (c) Preparation of test battery The test battery has a rated voltage of 2V and a rated 5-hour rate capacity of 32Ah. The plate assembly of the test battery consists of seven positive plates and seven negative plates. The negative plates are housed in a pouch-shaped separator made of a microporous polyethylene film and are stacked alternately with the positive plates to form a plate assembly. The plate assembly is housed in a polypropylene container together with an electrolyte (aqueous sulfuric acid solution) and chemically treated in the container to create a liquid-type lead-acid battery. The specific gravity of the electrolyte in a fully charged lead-acid battery at 20°C is 1.28.

[0165] (2) Evaluation (a) Evaluation of the amount of overcharged electricity Using the above test battery (lead-acid battery), the overcharge quantity of electricity is measured under the following conditions. In order to create more overcharge conditions than the normal 4-10 minute test specified in JIS D5301, a test of 1 minute of discharge and 10 minutes of charge (1-10 minute test) is performed at 75°C ± 3°C (high temperature light load test). The high temperature light load test is performed by repeating charge and discharge for 1220 cycles in the high temperature light load test. The overcharge quantity of electricity (charge quantity of electricity - discharge quantity of electricity) in each cycle up to the 1220th cycle is added up to find the integrated value (Ah) of the overcharge quantity of electricity. The overcharge quantity of electricity of each lead-acid battery is evaluated as a ratio when the integrated value (Ah) of the overcharge quantity of electricity of lead-acid battery R1 is set to 100%. Discharge: 25A, 1 minute Charging: 2.47V / cell, 25A, 10 minutes Water tank temperature: 75℃±3℃

[0166] (b) Low-temperature, high-rate discharge performance after light-load testing The test battery after the high-temperature light-load test in (a) above is fully charged and discharged at a discharge current of 150A at -15°C until the terminal voltage reaches 1.0V / cell. The discharge time (s) at this time is the discharge duration of the low-temperature high-rate discharge after the light-load test. The longer the discharge duration, the better the low-temperature high-rate discharge performance. The low-temperature high-rate discharge performance of each battery is evaluated as a ratio (%) when the discharge duration of lead-acid battery R1 is set to 100.

[0167] (c) Loss of electrolyte Measure the mass (M0) of the test battery. Charge the test battery at a constant voltage of 14.4 V with a maximum current of 50 A for 84 days in a water bath at 60°C ± 5°C. After charging, remove the test battery from the water bath and leave it to cool to room temperature (20-35°C), then measure the mass (M1) of the test battery. Calculate the amount of electrolyte loss by subtracting M1 from M0. Evaluate the amount of electrolyte loss for each battery as a percentage, assuming the amount of electrolyte loss in battery R1 to be 100.

[0168] The production conditions and some of the evaluation results are shown in Table 1. In Table 1, "PEG ester" refers to an ester of polyethylene glycol, specifically, polyoxyethylene oleate. The polyoxyethylene oleate is C 17 H 33 It is a polymer compound represented by the formula COO(-CH2-CH2-O)5-H. In Table 1, "PPG" is polypropylene glycol (number average molecular weight of about 2000).

[0169] [Table 1]

[0170] In the batteries A1 to A6, the content of the polymer compound (P) in the first negative electrode material arranged in the center of the negative electrode plate is greater than the content of the polymer compound (P) in the second negative electrode material arranged on the surface of the negative electrode plate. On the other hand, in the batteries C1 to C6, the polymer compound (P) is substantially uniformly dispersed in the negative electrode material. The negative electrode material of the battery R1 does not contain the polymer compound (P).

[0171] Among the results in Table 1, the results of the overcharge quantity of electricity are shown in FIG. 4, and the results of the low-temperature high-rate discharge performance after the light load test are shown in FIG. 5. As shown in Table 1 and FIG. 4, when the type of polymer compound (P) is the same and the content of the polymer compound (P) in the entire negative electrode material is the same, the overcharge quantity of electricity of the batteries A1 to A6 is lower than that of the corresponding batteries C1 to C6. This is considered to be due to the above-mentioned reason (paragraph 0018). Note that the batteries A1 to A6 and the batteries C1 to C6 to which the polymer compound (P) is added all have a lower overcharge quantity of electricity than the battery R1.

[0172] As shown in Table 1 and Figure 5, when the type of polymer compound (P) is the same and the content of the polymer compound (P) in the entire negative electrode material is the same, the low-temperature high-rate discharge performance of the batteries A1 to A6 is higher than that of the corresponding batteries C1 to C6. This is believed to be due to the reasons described above (paragraph 0019). In the batteries A1 to A6, the decrease in low-temperature high-rate discharge performance when the content of the polymer compound (P) in the entire negative electrode is increased is significantly smaller than that of the batteries C1 to C6.

[0173] Comparing the batteries A1 to A3 with the batteries A4 to A6, the batteries using an ester of polyethylene glycol rather than polypropylene glycol have a lower overcharge quantity of electricity and higher low-temperature high-rate discharge performance.

[0174] Batteries A1 to A3 are compared with batteries C1 to C3, and battery A5 is compared with battery C5. When the type of polymer compound (P) is the same and the content of the polymer compound (P) in the entire negative electrode material is the same, the battery in which the polymer compound (P) is added to the center of the negative plate has a smaller amount of electrolyte loss (amount of electrolyte loss) than the battery in which the polymer compound is added uniformly to the entire negative plate. Comparing battery A2 with battery A5, the amount of electrolyte loss can be reduced by using an ester of polyethylene glycol rather than polypropylene glycol.

[0175] Lead-acid batteries A7 and C7 Batteries A7 and C7 are produced in the same manner as the production method of lead-acid battery A1, except that the mass-based content of the polymer compound (P) in the first negative electrode material and the second negative electrode material is changed as shown in Table 2. The same polymer compound as that used in battery A1 is used as the polymer compound (P). Table 2 shows some of the production conditions and evaluation results.

[0176] [Table 2]

[0177] In the battery A7, the content of the polymer compound (P) in the second negative electrode material is about 0.5 times the content of the polymer compound (P) in the first negative electrode material. The overcharged quantity of electricity of the battery A7 is lower than that of the battery C7, and the battery A7 exhibits good characteristics. In addition, the low-temperature high-rate discharge performance of the battery A7 is better than that of the battery C7. The reduction in the electrolyte of the battery A7 is smaller than that of the battery C7.

[0178] As described above, according to the present invention, a lead-acid battery having a particularly low overcharged quantity of electricity can be obtained. Furthermore, according to the present invention, a lead-acid battery having a particularly low overcharged quantity of electricity and high low-temperature high-rate discharge performance can be obtained. [Industrial Applicability]

[0179] The present invention can be used for lead-acid batteries. The lead-acid battery of the present invention is suitable for use in idling-stop vehicles as an IS lead-acid battery that is charged and discharged under PSOC conditions. The lead-acid battery can also be suitably used as a starting power source for vehicles (such as automobiles and motorcycles) and industrial power storage devices (such as power sources for electric vehicles (such as forklifts)). These uses are merely examples and are not limited to these uses. [Explanation of symbols]

[0180] 1:Lead acid battery 2: Negative plate 2a: Negative electrode current collector 2aa: Linear part 2b: Negative electrode material 2b1: First negative electrode material 2b2: second negative electrode material 3: Positive plate 4: Separator 5: Positive electrode shelf 6: Negative electrode shelf 7: Positive pole 8: Through connector 9: Negative pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Negative terminal 17: Positive terminal 18: Liquid outlet plug

Claims

1. A positive electrode plate and a negative electrode plate are included. The negative electrode plate includes a negative electrode current collector and a negative electrode material supported on the negative electrode current collector, the negative electrode material includes a first negative electrode material and a second negative electrode material disposed outside the first negative electrode material, the content (ppm) of the polymer compound in the first negative electrode material is greater than the content (ppm) of the polymer compound in the second negative electrode material; The polymer compound is oxyC 2-4 Contains a repeating structure of alkylene units, A lead-acid battery, wherein the content of the polymer compound in the first negative electrode material is in the range of 80 ppm to 500 ppm by mass.

2. The polymer compound is 2-4 2. The lead acid battery according to claim 1, comprising at least one selected from the group consisting of a hydroxy compound containing the repeating structure of an alkylene unit, an etherified product of the hydroxy compound, and an esterified product of the hydroxy compound.

3. The lead acid battery according to claim 1, wherein the polymer compound comprises an ester of a polyalkylene glycol having an alkylene group with a carbon number of 2 to 4.

4. The negative electrode current collector includes a plurality of linear portions, The lead-acid battery according to any one of claims 1 to 3, wherein the first negative electrode material is disposed in gaps between the plurality of linear portions.

5. The lead-acid battery according to claim 4 , wherein the negative electrode current collector has a grid portion constituted by the plurality of linear portions.

6. The mass-based content (ppm) of the polymer compound in the second negative electrode material is in the range of 0 to 0.7 times the mass-based content (ppm) of the polymer compound in the first negative electrode material. The lead-acid battery according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Machine for attaching rivet * button and analogues

    JP1979024145A

  • Manufacture of positive plate for lead storage battery

    JP1984042771A

  • Plate for thin type lead-acid battery and manufacture thereof

    JP1994196157A

  • Negative electrode plate for lead-acid battery and lead-acid battery

    JP1997147874A

  • Lead-acid battery, and additive therefor

    JP2000149981A